ANALISIS DISTRIBUSI TEGANGAN PADA SISTEM SUSPENSI DEPAN MINIBUS DENGAN BEBAN BERVARIASI - Harahap, Jagodang; Mizan, khairol; Pribadyo, Pribadyo (AUSTENIT, 2024)
The suspension system when dampening coil spring shocks experiences stress which can affect service life. The aim of this research is to analyze the stress distribution that occurs in the coil springs of the front wheels of minibuses at varying carrying loads, namely 1,185 kg, 1,395 kg and 1,735 kg. Strain data is recorded using a strain gauge on the coil spring, then the strain signal is converted into stress and then used to analyze the stress distribution using the Finite Element Method. The research results show that the stress distribution value increases as the load increases, meaning that the stress distribution at a carrying load of 1,735 kg increases by 63%. Furthermore, for a carrying load of 1,395 kg it is 61% and at a carrying load of 1,185 kg it is 39% of the yield strength of the SAE 5160 material. From the three variations in loading given, it was found that locations prone to fatigue occur on the inner side of the inner second winding from the top of the coil spring.